Evaluation of two transformation protocols for Crambe hispanica subsp. abyssinica - Jeppsson, Simon (SLU/Dept. of Plant Breeding (from 130101), 2015)
BACKGROUND: Crambe is an oil-crop suitable for industrial purposes and breeding aiming at producing novel oil-qualities may be achieved by genetransformation. Understanding the synthesis of fatty acids and an efficient transformation protocol is of pivotal role in this context. Two transformation protocols (Agrobacterium mediated according Bang-Quang Huang and oral dip according Clough and Bent 1998) for crambe are evaluated, and a RNAi construct is produced aiming to down-regulate CaDGAT1. RESULTS: None of the evaluated transformation protocols produce any successfully transformed plants during this evaluation. CaDGAT1 is partially sequenced and a RNAi construct for CaDGAT is produced, while the functionality of the construct is un-validated. CONCLUSIONS: Alternative Agrobacterium mediated transformation protocols published by Li et al. 2010 have managed to transform crambe successfully but a functional oral dip protocol may be even more cost effective. more studies on oral dip must be carried out to evaluate this however.